Computer graphics : (Addison-Wesley, 1990)
The long-awaited second edition of this book has been completely rewritten to provide the most comprehensive authoritative and up-to-date coverage of the field---making it the standard computer graphics reference work for the 1990s. The authors provide a unique combination of current concepts and practical applications. The important algorithms in 2D and 3D graphics are detailed for easy implementation.